THE IMPLEMENTATION OF THE REQUIREMENTS OF THE UNITED NATIONS CONVENTION AGAINST CORRUPTION IN UZBEKISTAN - Kabilov Sharif Rakhimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article studies and analyzes the practice of the requirements of the United Nations (UN) Convention against Corruption in Uzbekistan.